Hydrologic Habitus: Wells, Watering Practices, and Water Supply Infrastructure. Issue 1 (1st March 2020) - Ternes, Brock; Donovan, Brian
Abstract : Private water wells and municipal water supplies function as different systems of water provision, creating distinct—but understudied—patterns of water consumption. This article examines private well ownership to assess the relationships among conspicuous water consumption, cultural practices, and environmental structures. We surveyed well owners and non-well owners throughout Kansas, a state highly reliant on groundwater (n = 864). Borrowing insights from Bourdieu's analysis of cultural consumption, this research considers the relationships between demographic variables and watering routines. We provide evidence that well ownership is a significant predictor of conspicuous water usage, and suggest attention to individuals' hydrologic habitus—a disposition toward water usage shaped by infrastructure, class, and pertinent social variables—facilitates a better understanding of well ownership, drought-time watering, and conspicuous water consumption.